Platelet factor 4 localization in carotid atherosclerotic plaques: correlation with clinical parameters - Pitsilos, Stephanie; Hunt, Jennifer; Mohler, Emile R.; Prabhakar, Anand M.; Poncz, Mortimer; Dawicki, Jennine; Khalapyan, Tigran Z.; L.Wolfe, Megan; Fairman, Ronald; Mitchell, Marc; Carpenter, Jeffrey; Golden, Michael A.; Cines, Douglas B.; Sachais, Bruce S. (Thrombosis and Haemostasis, 2003)
Emerging evidence supports a role for platelets in the progression of atherosclerosis in addition to an involvement in thrombotic vascular occlusion. Platelet Factor 4 (PF4), a chemokine released by activated platelets, stimulates several pro-atherogenic processes. Therefore, we examined the localization of PF4 and the homologous protein, Neutrophil Activating Protein-2 (NAP-2) in lesions representing the evolution of human atherosclerotic plaques. Carotid plaques from 132 patients with critical carotid stenosis and 6 autopsy specimens were studied. Clinical, histologic and immunohistochemical data were analyzed using a χ2-test. PF4 was detected in the cytoplasm of luminal and neovascular endothelium, in macrophages and in regions of plaque calcification. The presence of PF4 in macrophages and neovascular endothelium correlated with lesion grade (p = 0.004; p = 0.044). Staining of macrophages for PF4 correlated with the presence of symptomatic atherosclerotic disease (p = 0.028). In early lesions, PF4 was commonly found in macrophages of early lesions (Grade I/II), whereas NAP-2 was rarely present.In conclusion, correlation between PF4 deposition, lesion severity and symptomatic atherosclerosis suggests that persistent platelet activation may contribute to the evolution of athero-sclerotic vascular lesions. These studies support the rationale for the chronic use of anti-platelet therapy in patients at risk for developing symptomatic atherosclerosis.
Keywords: Atherosclerosis; platelet activation markers; vasculopathies; macrophage / phagocytosis